Factors Associated With the Prevalence of Prostate Cancer in Rural Saskatchewan: The Saskatchewan Rural Health Study. Issue 2 (12th August 2015) - Sharma, Meenu; Lawson, Joshua A.; Kanthan, Rani; Karunanayake, Chandima; Hagel, Louise; Rennie, Donna; Dosman, James A.; Pahwa, Punam; ,
Abstract: Purpose: Prostate cancer is the most commonly diagnosed cancer in Canadian males, and it is the third most common cause of cancer‐related deaths in men. Some studies suggest that occupational exposure may be associated with prostate cancer. However, the etiology of prostate cancer is ambiguous. The purpose of this study was to assess the rural occupational exposure, including farming, as a determinant of prostate cancer in rural men. We investigated the prevalence of prostate cancer and its putative relationship between rural exposures in the Saskatchewan province of Canada. Methods: In 2010, a baseline mailed survey was conducted of 11, 982 households located in 4 geographic regions (southwest, southeast, northwest, and northeast) of rural Saskatchewan, Canada. The questionnaires collected information on individual and contextual determinants from a rural population of men. In total 2, 938 males older than 45 years were included in the logistic regression analysis. Findings: The age‐standardized prevalence of prostate cancer was 3.32%. Farm residence was a significant risk factor associated with prevalence of prostate cancer while farming occupation and duration were not. Men who were exposed to insecticides and fungicides together (OR [95% CI] = 2.23 [1.15‐4.33], P = .02) at work showed an increased potential risk compared to the nonexposed. The effect of farm/nonfarm residence on prevalence of prostate cancer differed depending on personal smoking history and family history of cancer. Conclusion: Workplace exposure to insecticides and fungicides together were statistically significantly associated with prevalence of prostate cancer.